Effect of occupational activity on ambulatory blood pressure behaviour - Pereira, J (2020)
Hypertension (HBP) is a key risk factor for cardiovascular diseases, being strongly associated with behavioral and environmental aspects of living. Professional activities, amongst others that take place throughout the day, are responsible for important blood pressure (BP) variations and may increase it. Objective: This study aims at ascertaining the blood pressure profile and variation in teachers, during a typical teaching session. Methods: Ambulatory Blood Pressure Monitoring (ABPM) was performed in a cohort of 21 university teachers during a typical professional day, comprising the following periods: 24-hour period, day period, night period, morning period, 2 hours before class, during class, 2 hours after class, aerobic exercise period and 1 hour after exercise period. Results: Teachers demonstrated higher BP during the occupational activities (137.71 / 88.57 mmHg) compared to the period before (128.81 / 82.43 mmHg) and after the class (132,38 / 85, 19 mmHg) (p <0.05). It was found that systolic BP has the greatest variability across the considered activities and time periods. In a gender analysis, men had higher systolic BP compared to women (141.55 mmHg / 133.50 mmHg, respectively), and demonstrated greater variability across activities. Conclusions: The results clearly demonstrated the existence of important variations in BP due to different daily activities. The occupational period produced a significant increase in the different components of BP and heart rate. The long-term effects of repeated exposure to this increase in BP related with the occupational contexts remains to be demonstrated.